Aktivitas Wisatawan Generasi Z Di Pantai Melasti Ungasan, Kecamatan Kuta Selatan, Kabupaten Badung, Bali - Elsampurno, Virena Michelle; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA, 2024)
Melasti Beach, located in Ungasan Village, Bali, is renowned for its stunning natural beauty, excellent facilities, and diverse attractions. This beach offers natural attractions like white sand and breathtaking scenery, cultural attractions such as the Kecak Titi Situ Banda Dance performance, and artificial attractions including a beach club. This study aims to identify the preferences of Generation Z in selecting existing attractions and the activities they engage in at the Melasti Beach Tourist Attraction. Using qualitative methods, the study gathers data through observation, interviews, and documentation. The results reveal that Generation Z visits Melasti Beach primarily to relax and explore new experiences. Their activities often include sunbathing, swimming, attending cultural performances, and socializing at the beach club. To enhance the appeal of Melasti Beach for Generation Z, sustainable management practices must be adopted. These practices can include maintaining the cleanliness of the beach, preserving the natural environment, and offering new and innovative attractions that cater to the interests of young visitors. By understanding and catering to the preferences of Generation Z, Melasti Beach can continue to thrive as a popular tourist destination. Ensuring a balance between natural preservation and modern amenities will be key in achieving long-term sustainability. The insights from this study can guide the development of strategies that not only attract more Generation Z tourists but also promote the overall sustainable development of the Melasti Beach Tourist Attraction. Keywords: Melasti Beach, Ungasan Village, Bali, Generation Z, Tourist Attractions, Tourist Activities